International Expansion based on a Locally Authentic Brand: Issues and Findings from Italian Case Studies - Ranfagni, Silvia; Sarti, Daria; Runfola, Andrea (Journal of Marketing Development and Competitiveness, 2018)
This paper deals with the topic of brand authenticity in the internationalization of a company. It aims at addressing authenticity by proposing the consideration of this concept, its relationships with the one of “made in”, the role of local heritage as well as the internal management of the ‘process’ that combines internationalization with authentic brand values. The paper proposes some preliminary findings and implications regarding the two main research questions: a) How does brand authenticity that is mainly focused on cultural heritage act as a driver of internationalization? and b) How does it relate with the “made in” concept?